Peran Lembaga Keuangan Syariah Dalam Mendorong Pertumbuhan Ekonomi : Studi Pustaka Berbasis Ekonomi Makro Islam - Ristiyanti Ahmadul Marunta; Nahda Afniatul Ataya; Anggun Pratiwi; Mustabsyirah Mustabsyirah; Nur Asisah (Economics and Digital Business Review, 2025)
This study aims to analyze the role of Sharia Financial Institutions (SFIs) in promoting economic growth in Indonesia through sharia-based financing and social fund management. This study uses a descriptive qualitative method with a library research approach, which examines relevant literature, scientific journals, and official documents related to the activities and contributions of SFIs. The results of the study indicate that LKS play a significant role in promoting economic growth through interest-free financing of the real sector, empowering MSMEs, providing halal financial products and services, and managing zakat, infak, sedekah, and wakaf (ZISWAF) funds for social and economic purposes. Additionally, LKS have proven capable of expanding financial inclusion in remote areas and creating a more stable and equitable financial system. This study recommends that the government and policymakers continue to strengthen regulations, Islamic financial literacy, and support for digital innovation so that Islamic microfinance institutions can reach more segments of society and contribute more significantly to national economic development.